Hubungan Antara Disiplin Belajar dengan Hasil Belajarpada Mata Pelajaran Bahasa Indonesia Kelas IV Siswa Sekolah Dasardi Palembang - Sandi, Sandi; Akhbar, M. Taheri; Surmilasari, Nora (Institut Teknologi Pendidikan Indonesia, 2024)
The purpose of this study was to determine the Effect of Resistance Band and Pull Up Training on the Ability of 50 50-meter breaststroke Swimming in Prabumulih City Swimmers. This research method uses an experimental method with a two-group pretest-posttest research design. The sampling technique was taken randomly. Based on the results of this study, show that the t-test value of the resistance band group pretest and posttest is 4.608> 2.16 with a significance of 0.004> 0.05, meaning that there is a significant effect in resistance band training on the ability to swim 50 m breaststroke. The results of the t-test show that the t-test value of the pull-up group pretest and posttest is 7.050> 2.16 with a significance of 0.000> 0.05, meaning that there is a significant effect in pull-up training on the ability to swim 50 m breaststroke. There is a difference based on the average posttest resistance band training of 43.67 while pull-up training is 44.17.